Stability Assurance: RP-HPLC Method Development and Validation for Novel Dental Abscess Bulk Drugs Combinations - Kaushik, Dr. Aditi (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: This research focused on developing and validating a stability-indicating and RP-HPLC (Reverse Phase High-Performance Liquid Chromatography) method for the precise estimation of Metronidazole and Cefixime in bulk and formulation samples. The choice of Shim-pack C-18 column, with dimensions 250 X 4.6 mm then a particle size of 5 µm, was pivotal for achieving the desired chromatographic separation. The mobile phase used consisted of Methanol and Water in a ratio of 80:20 v/v. Results: The chromatographic conditions yielded excellent results, with retention times of 3.127 minutes for Metronidazole and 2.096 minutes for Cefixime. The method demonstrated linearity across a concentration range of 5 to 30 µg/mL for both compounds. Furthermore, the Limit of Detection (LOD) and Limit of Quantification (LOQ) values were determined as 0.331/1.004 µg/mL for Metronidazole and 0.590/1.789 µg/mL for Cefixime, respectively. Conclusion: In conclusion, the established RP-HPLC method underwent validation following ICH Q2 R1 guidelines to ascertain its accuracy, precision, and robustness. Its capacity to detect degradation products during stress testing, encompassing oxidation, photodegradation, acid, and base hydrolysis, validates it as a dependable stability-indicating technique. This method is suitable for the routine analysis of Metronidazole and Cefixime in pharmaceutical formulations, guaranteeing quality control and adherence to regulatory standards.